2017
DOI: 10.1039/c6ja00439c
|View full text |Cite
|
Sign up to set email alerts
|

Real-time elemental imaging of large dimension paintings with a novel mobile macro X-ray fluorescence (MA-XRF) scanning technique

Abstract: A novel mobile XRF scanner combining MA-XRF and micro-XRF techniques and allowing near real-time elemental imaging of macroscopic paintings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(65 citation statements)
references
References 19 publications
0
65
0
Order By: Relevance
“…The elemental distribution images of the two paintings were obtained by a novel scanning technique allowing a real‐time imaging of large‐dimension artworks, the possibility made real only after the point XRF analysis has been already carried out . The MA‐XRF scanner was developed at the LANDIS laboratory of CNR‐IBAM and INFN‐LNS in Catania (Italy).…”
Section: Methodsmentioning
confidence: 99%
“…The elemental distribution images of the two paintings were obtained by a novel scanning technique allowing a real‐time imaging of large‐dimension artworks, the possibility made real only after the point XRF analysis has been already carried out . The MA‐XRF scanner was developed at the LANDIS laboratory of CNR‐IBAM and INFN‐LNS in Catania (Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Most recent optimising of MA‐XRF scanners includes the use of two or four detectors, allowing higher resolution and consequently shorter measuring times. For example, Romano et al reported a lateral resolution of up to 25 μm, scanning at a speed of 100 mm s −1 with 500 μm pixel size . Thurrowgood et al presented 31.6 megapixel high‐definition XRF mapping using synchrotron source .…”
Section: Introductionmentioning
confidence: 99%
“…Elemental imaging using X-ray fluorescence is a non destructive technique capable of bringing out important information in many fields [1], from materials science to cultural heritage [2][3][4][5] and planetary surface analysis [6] . A first class of methods by which X-ray fluorescence images can be obtained consists in the two dimensional scanning of a beam on the object and collection of the fluorescence X-rays at every point of the map [7,8]. It requires a focusing device and a minimum of two-axis motorized scanner.…”
Section: Introductionmentioning
confidence: 99%